College algebra worktext - Jesuitas, Reynaldo M.; Valderama, Julius S.; Morales, Jomar P.; Santos, Everson J.; Daez, Francisco D. (Mutya Publishing House, Inc., 2013)
"The primary aim of this book is to equip students with skills in computation, reasoning, and problem solving to prepare them with thorough foundation for further study in mathematics, sciences, and engineering"--Preface.